Lichen Sebagai Bioindikator Pencemaran Udara Di Gerbang Kota (Gateway) Kota Jambi - Febri Juita Anggraini; Ria Resti Oktapiani; Freddy Ilfan; Zuli Rodhiyah (Jurnal Daur Lingkungan, 2021)
The gateway of city is the point of entry and exit for traffic activities, the high traffic activity that occurs causes air pollution, thereby reducing air quality. The use of lichen as a bioindicator is considered more efficient than using other indicator tools or machines. Purpose of this study was to determine the level of air pollution at the gateway of Jambi city using lichen as a bioindicator and to determine the concentration of Pb metal content in lichen. The research method used is exploration with roaming methods. The location of the research was carried out at the West Gate of Simpang Rimbo, the South Gate of Paal 10, and the East Gate of Aurduri 2. The Pb metal test in lichen was carried out using Inductively Coupled Plasma Mass Spectroscopy analysis method (ICP-MS). Based on the measurement results, the Aurduri 2 location is included in the location of low traffic density with an average number of 18,509 vehicles/ day. The location with moderate traffic density is Paal 10 with an average number of 31,941 vehicles/ day. The vehicle traffic density with the highest number was the Simpang Rimbo location with an average number of 45,041 vehicles/ day. The highest concentration of Pb in lichen was at the Aurduri 2 sampling location with a Pb metal value of 3.01 ppm and the lowest at the Simpang Rimbo location of 2.31 ppm.